Clinical and epidemiological characteristics resistant hypertension in the practice of family doctor - Busel, S. V. (Journal of Education, Health and Sport, 2017)
Busel S.V. Clinical and epidemiological characteristics resistant hypertension in the practice of family doctor. Journal of Education, Health and Sport. 2016;6(11):702-714. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.225448 http://ojs.ukw.edu.pl/index.php/johs/article/view/4122 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. Clinical and epidemiological characteristics RESISTANT HYPERTENSION IN THE PRACTICE OF FAMILY DOCTOR S. V. Busel Odessa National Medical University Summary Arterial hypertension (AH) is one the most extensive cardio-vascular risk factors all over the world. According to present day statistics 31.5% of Ukrainian adult population have arterial blood pressure (ABP) higher norm. Resistant AH is aa widely spread clinical problem and its faced by both general practioners and specialists. The presence of non-controlled AH increases cardio-vascular risk, promotes early and significant damage of target organs and tissues. Thus, the studies of resistant AH directed to optimization of pseudo-resistant AH differentional diagnostics and resistant AH are of top urgency. The investigations done highlighted a lot of complaints, higher figures of ABP, decrease of quality of life, comorbid pathology was met more often. Key words: resistant hypertension, pseudo-resistant hypertension.